Examining the Australian Digital Platforms Inquiry and theorizing 'accidental policy'. (1st June 2021) - Picard, Robert G.; Park, Sora
'Accidental policy' is a term often used to disparage unplanned or under-deliberated policy, but it can also be used as a concept to define and theorize policy development and its effects more broadly. This article does the latter by applying the accidental policy lens to the case of the Australian Digital Platforms Inquiry ‐ the first of its kind worldwide ‐ and then uses elements from the development and effects of the inquiry to theorize the concept for application in other policy studies. This article examines the factors ‐ including existing media, communications, technology developments and policies and political manoeuvring ‐ that led Australia to confront large multinational platforms and become a world leader in digital platforms policy. Rather than the continuation of a long-term, consistent policy regime, the inquiry resulted from political expediency and behind-the-scenes parliamentary deal making. This article provides an analysis of a situation in which a deliberative policy process did not occur but a significant policy impetus was still developed. This study adds to the understanding of accidental policy making in which a rapid response to external pressures, as well as more complex factors including political negotiation and deal making, is at play.